Optimizing land use decision-making to sustain Brazilian agricultural profits, biodiversity and ecosystem services. (December 2016) - Kennedy, Christina M.; Hawthorne, Peter L.; Miteva, Daniela A.; Baumgarten, Leandro; Sochi, Kei; Matsumoto, Marcelo; Evans, Jeffrey S.; Polasky, Stephen; Hamel, Perrine; Vieira, Emerson M.; Develey, Pedro Ferreira; Sekercioglu, Cagan H.; et al.
Abstract: Designing landscapes that can meet human needs, while maintaining functioning ecosystems, is essential for long-term sustainability. To achieve this goal, we must better understand the trade-offs and thresholds in the provision of ecosystem services and economic returns. To this end, we integrate spatially explicit economic and biophysical models to jointly optimize agricultural profit (sugarcane production and cattle ranching), biodiversity (bird and mammal species), and freshwater quality (nitrogen, phosphorus, and sediment retention) in the Brazilian Cerrado. We generate efficiency frontiers to evaluate the economic and environmental trade-offs and map efficient combinations of agricultural land and natural habitat under varying service importance. To assess the potential impact of the Brazilian Forest Code (FC), a federal policy that aims to promote biodiversity and ecosystem services on private lands, we compare the frontiers with optimizations that mimic the habitat requirements in the region. We find significant opportunities to improve both economic and environmental outcomes relative to the current landscape. Substantial trade-offs between biodiversity and water quality exist when land use planning targets a single service, but these trade-offs can be minimized through multi-objective planning. We also detect non-linear profit-ecosystem services relationships that result in land use thresholds that coincide with the FC requirements. Further, we demonstrate that landscape-level planning can greatly improve the performance of the FC relative to traditional farm-level planning. These findings suggest that through joint planning for economic and environmental goals at a landscape-scale, Brazil's agricultural sector can expand production and meet regulatory requirements, while maintaining biodiversity and ecosystem service provision. Highlights: Strategic land use achieves agricultural and environmental goals in the Cerrado. Optimal outcomes occur when land use targets biodiversity and ecosystem services. Landscape (relative to farm) planning improves economic and environmental outcomes. Multi-objective planning at larger spatial scales can promote sustainability.